Hypothetical proteins as predecessors of long non-coding RNAs - Malik, Girik; Agarwal, Tanu; Raj, Utkarsh; Sundararajan, Vijayaraghava Seshadri; Bandapalli, Obul Reddy; Suravajhala, Prashanth (Current genomics, 2020)
Hypothetical Proteins [HP] are the transcripts predicted to be expressed in an organism, but no evidence of it exists in gene banks. On the other hand, long non-coding RNAs [lncRNAs] are the transcripts that might he present in the 5' UTR or intergenic regions of the genes whose lengths are above 200 bases. With the known unknown [KU] regions in the genomes rapidly existing in gene banks, there is a need to understand the role of open reading frames in the context of annotation. In this commentary, we emphasize that HPs could indeed he the predecessors of lncRNAs.